Carnografi: David Cronenberg og skriften på kødet - Krogholm, Claus (Academic Quarter | Akademisk kvarter, 2010)
Claus Krogholm Carnografi – David Cronenberg og skriften på kødet. (Carnography – David Cronenberg and the writing on the flesh). Carnography is a neologism for writing, films, images, or other material that contains gratuitous amounts of bloodshed, violence and/or weaponry. The article is about the film director David Cronenberg´s use of flesh. After defining the concept of carnography and describing its very literal use in Franz Kafka the article characterizes the director´s interest in new flesh in Cronenberg´s central films. New flesh is about the fusion of man and technology, the organic and the inorganic, flesh and metal. This leads to an analysis of the recent film Eastern Promises and the use of the writing on the flesh in this film – tattoos. The conclusion is that in general Cronenberg is interested in problems of identity, which gets its own expression in tattoos that are only ’skin deep’.